2014
DOI: 10.1177/0193723514557822
|View full text |Cite
|
Sign up to set email alerts
|

The International Olympic Committee–International Paralympic Committee Relationship

Abstract: The inclusion of athletes with a disability into the Olympic Games has been a longstanding issue within the Paralympic Movement. This article reviews the history of including athletes with a disability into the Olympic Games using two frameworks, the Critical Change Factors Model (CCFM) and its companion, the Organizational Continuum for the Inclusion of Identity Groups in Sport (OCIIS). The CCFM and OCIIS were developed by Fay, grounded in critical social, principal-agent, and open systems theories. Last, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 35 publications
1
5
0
1
Order By: Relevance
“…Therefore, the issue of no one caring about the disabled involvement in sports was moderate. This is in agreement with (Legg et al, 2015) which identified negative attitudes towards people with a disability as the major determinant of sports participation or non-participation within a developing country context. From open-ended questions, St34 stated that "the university has no sports for the students with disabilities while St35 said that, it has not done enough to pitch sports for the disabled".…”
Section: Challenges Faced When Including Students With Disability In ...supporting
confidence: 90%
“…Therefore, the issue of no one caring about the disabled involvement in sports was moderate. This is in agreement with (Legg et al, 2015) which identified negative attitudes towards people with a disability as the major determinant of sports participation or non-participation within a developing country context. From open-ended questions, St34 stated that "the university has no sports for the students with disabilities while St35 said that, it has not done enough to pitch sports for the disabled".…”
Section: Challenges Faced When Including Students With Disability In ...supporting
confidence: 90%
“…More recently, the Paralympic Games held in Rio de Janeiro, Brazil in 2016 had 22 sports modalities, 4,328 athletes from 159 countries and 528 medals [1]. This competition is the main international multisport event for participants with the most diverse physical and intellectual impairments, which include athletes with spinal-cord injuries, visual impairment, amputations, and cerebral palsy [2,3]. These games are organized by the International Paralympic Committee (IPC) which invests a lot of effort and financial resources in an attempt to obtain better results and, consequently, better rankings in the medal Ranking [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, litigation can also prompt sport organizations to review and update policies and procedures to be more inclusive organizations. For example, even though Scot Hollonbeck's suit against the U.S. Olympic Committee (Hollonbeck v. United States Olympic Committee, 2008) under both Section 504 and the ADA was unsuccessful in compelling benefits for Paralympic athletes similar to those provided Olympic athletes, it produced the necessary environment to engage Olympic and Paralympic stakeholders to implement new policies and practices to provide for more equal development of Paralympic sports and athletes (Legg, Fay, Wolff, & Hums, 2015).…”
Section: Policy Development and Inclusionmentioning
confidence: 99%